2020
DOI: 10.1002/jcpy.1200
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Costs versus Actual Benefits of Demographic Self‐Disclosure in Online Support Groups

Abstract: Millions of U.S. adults join online support groups to attain health goals, but the social ties they form are often too weak to provide the support they need. What impedes the strengthening of ties in such groups? We explore the role of demographic differences in causing the impediment and demographic self-disclosure in removing it. Using a field study of online quit-smoking groups complemented by three laboratory experiments, we find that members tend to hide demographic differences, concerned about poor socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 97 publications
(187 reference statements)
0
13
0
6
Order By: Relevance
“…La participation, c'est-à-dire la génération de contenu, est à l'origine de toute communauté ; elle est la condition sine qua non de l'existence de ces rassemblements (Bagozzi et Dholakia, 2002 ;Ind et al, 2013 ;Pechmann et al, 2021). Elle est définie comme le fait d'avoir un rôle actif dans la construction de relations (Ind et al, 2013).…”
Section: Les Communautés En Ligne De Soutien à La Perte De Poidsunclassified
“…La participation, c'est-à-dire la génération de contenu, est à l'origine de toute communauté ; elle est la condition sine qua non de l'existence de ces rassemblements (Bagozzi et Dholakia, 2002 ;Ind et al, 2013 ;Pechmann et al, 2021). Elle est définie comme le fait d'avoir un rôle actif dans la construction de relations (Ind et al, 2013).…”
Section: Les Communautés En Ligne De Soutien à La Perte De Poidsunclassified
“…In this respect, Pechmann et al (2021) investigated the role support groups play in facilitating goals regarding why consumers join those groups. In the context of online communities, where self‐disclosures may be a way to build trust in the community, the authors consider how self‐disclosures regarding differences between group members are made.…”
Section: Reconceptualizing Prosocial Behavior As Intersocialmentioning
confidence: 99%
“…Whereas Pechmann et al (2021) reported positive interpersonal outcomes in online communities, Pundak et al (2021) found that consumers can also engage in public shaming of wrongdoers. This observation raises interesting questions such as whether actions that benefit more people by discouraging bad behavior but hurt an individual are prosocial, when are these actions prosocial, and whether such actions can be considered prosocial when other actions could also have discouraged bad behaviors.…”
Section: Reconceptualizing Prosocial Behavior As Intersocialmentioning
confidence: 99%
“…Therefore, self-disclosure on short video applications may be considered as a general pattern of behavior in the context of large audiences. With the increase in individual self-disclosure information and the construction of user identities (Pechmann et al, 2021 ), individuals with a strong desire to be identified with the public tend to use strategies that are perceived as positive and worthy of replication to demonstrate desirable characteristics and behaviors, thereby attracting more disclosure (Rosenberg and Egbert, 2011 ; Wei and Liu, 2020 ).…”
Section: Theoretical Foundation and Hypothesis Developmentmentioning
confidence: 99%
“…Self-disclosure is the act of making oneself known to the public; it was the process by which individuals actively reveal personal information, and this process can trigger perceived similarity among the public (Solomonov and Barber, 2019 ). Good interaction between users on short video applications positively affects perceived similarity, which in turn generates interpersonal attraction and raises relationship levels (Pechmann et al, 2021 ). In particular, when the self-disclosure information is more adequate, it will lead to more people perceiving stronger similarity and thus higher perceived similarity to the individual who publicly discloses the information.…”
Section: Theoretical Foundation and Hypothesis Developmentmentioning
confidence: 99%